A Method to Assess Linkage Disequilibrium between CNVs and SNPs Inside Copy Number Variable Regions - Wineinger, Nathan E.; Pajewski, Nicholas M.; Tiwari, Hemant K. (Frontiers in Genetics, 2011)
Since the discovery of the ubiquitous contribution of copy number variation to genetic variability, researchers have commonly used metrics such as r-squared to quantify linkage disequilibrium (LD) between copy number variants (CNVs) and single nucleotide polymorphisms (SNPs). However, these reports have been restricted to SNPs outside copy number variable regions (CNVR) as current methods have not been adapted to account for SNPs displaying variable copy number. We show that traditional LD metrics inappropriately quantify SNP/CNV covariance when SNPs lie within copy number variable regions (CNVR). We derive a new method for measuring LD that solves this issue, and defaults to traditional metrics otherwise. Finally, we present a procedure to estimate CNV-SNP allele frequencies from unphased CNV-SNP genotypes. Our method allows researchers to include all SNPs in SNP/CNV LD measurements, regardless of copy number.